ADAB BERGAUL SESAMA MAKHLUK (DENGAN TEMAN) DALAM KITAB BIDAYATUL HIDAYAH SERTA DAMPAKNYA DALAM MENCEGAH BULLYING DI SEKOLAH - Siti Rahmawati; Ahmad Kusyairi (Program Studi PGMI STAI Al Falah Banjarbaru, 2025)
This study aims to examine the etiquette of social interaction (adab) with fellow beings, specifically in the context of friendship, as contained in the book Bidayatul Hidayah by Imam Al-Ghazali, and to analyze its relevance in efforts to prevent bullying in the school environment. Furthermore, this research explores the supporting and inhibiting factors in implementing these etiquettes within students' social lives. This research employs a qualitative approach with a library research method, where the primary data is obtained from the book Bidayatul Hidayah. It is supported by classical literature such as Adab al-Mufrad, Taisir al-Khallaq, and Washaya al-Abaa lil Abna’i, as well as contemporary references such as the books Anti Bullying: Pendekatan Psikologis (Anti-Bullying: A Psychological Approach) and Melawan Bullying (Against Bullying). The analysis is conducted descriptively and critically using content analysis techniques based on the themes of etiquette and bullying prevention. The results show that social etiquettes, such as guarding one’s speech, avoiding hurting friends, honesty in heart and deed, and not spreading others' flaws, have a positive impact on creating a harmonious social environment free from bullying. The implementation of these etiquettes is supported by religious education, the roles of teachers and parents, and an Islamic school culture. Meanwhile, the obstacles include students' lack of understanding of adab, the influence of social media, and an unsupportive school environment. Thus, the etiquettes found in classical texts can serve as a foundation to strengthen character education and prevent bullying in schools sustainably.